European Support for NATO: Strong But Not Unshakable. - United States. Department of State. Office of Research.; Carriere, Erin. (Tufts University. Tisch Library., 2019)
Traditionally supportive of NATO, European publics rallied behind the campaign against terrorism immediately after September 11th and are still supportive of both today. However, while strong and deep, European commitment to NATO is not unconditional. Europeans largely want a future NATO that has more members and close ties to Russia, and in which the EU has a greater role. The U.S. has asked the Europeans to take on a greater role, but now needs to nurture this commitment - or at least not undermine it through 'unilateralist' measures (Kyoto, ICC, Middle-East) that may fritter away European support.; [Opinion Analysis] M-96-02